Caribbean Report 27-03-1997 - Orr, Carol (anchor); Fraser, Tony (correspondent); Maraj, Ralph (interviewee); Khan, Sharief (correspondent); Joseph, Theophilus (interviewee); Jones, Owen Bennett (correspondent); Rowe, Yvette (correspondent) (The British Broadcasting Corporation, 1997)
When Caricom leaders meet President Clinton in May, the deportation from the United States of Caribbean born people with a criminal record will be a major item for discussion. Next, investigators today began trying to identify the bodies of 39 cult members who apparently committed suicide in San Diego, South California. There are parallels with the Jonestown Massacre in Guyana. Next, in Bermuda the swearing in of the new premier took place today. She is the youngest and first female premier in the island. Next, in St Lucia a leading churchman has called on politicians to keep politics out of lent. He has expressed concern that political campaigning is going on during this time. Next, in Haiti, in order to avoid greater social unrest in the country the government may have to adopt a different approach to its privatisation programme. Next, still in Haiti, the United Nation’s independent expert on the situation of human rights in Haiti has compiled a report for the United Nation Human Rights Commission. The report gives recommendations on how to better protect human rights in the impoverished Caribbean state. Next, Peru’s President has confirmed that talks with the rebels holding seventy two hostages in Lima have progressed toward a solution. Proposals include asylum for the hostages in Cuba or the Dominican Republic, freedom for some imprisoned MARTA members and payment of a war tax to the hostage takers. The concluding segment ends with Stories of Caribbean interest appearing in the British press
1. Headlines (00:00-00:31)
2. The Deportation of Caribbean criminals to be discussed when Caricon leaders meet President Clinton in May. Ralph Maraj, Trinidad and Tobgao Foreign Minister is interviewed. Tony Fraser reports from Port of Spain. (00:31-02:39)
3. Echoes of Guyana's Jonestown massacre as details of San Diego mass suicide emerge. Sharief Khan reports. (02:40-07:15)
4. Pamela Gordon is sworn in as Bermuda's new Premier. George Rushe reports from Bermuda (07:16-08:54)
Keywords: Deportation of Criminals -- Caribbean.; Leaders -- Caricom.; Clinton, Bill.; Jonestown massacre.; Cult -- California.; Gordon, Pamela.; Churchman -- St Lucia.; Lent -- St Lucia.; Privatisation -- Haiti.; Human rights -- Haiti.; Peruvian rebels.